Lysosomal-targeted doxorubicin delivery using RBC-derived vesicles to overcome drug-resistant cancer through mitochondrial-dependent cell death - Chih-Peng Lin; Shu-Hui Wu; Tzu-Yin Lin; Chia-Hui Chu; Leu-Wei Lo; Ching-Chuan Kuo; Jang-Yang Chang; Szu-Chun Hsu; Bor-Sheng Ko; Ming Yao; Jong-Kai Hsiao; Shih-Wei Wang; et al. (Pharmacological Research, 2023)
Multidrug resistance (MDR) is a major challenge in cancer chemotherapy. Nanoparticles as drug delivery systems (DDSs) show promise for MDR cancer therapy. However, current DDSs require sophisticated design and construction based on xenogeneic nanomaterials, evoking feasibility and biocompatibility concerns. Herein, a simple but versatile biological DDS (bDDS) composed of human red blood cell (RBC)-derived vesicles (RDVs) with excellent biocompatibility was surface-linked with doxorubicin (Dox) using glutaraldehyde (glu) to form Dox-gluRDVs that remarkably suppressed MDR in uterine sarcoma through a lysosomal-mitochondrial axis-dependent cell death mechanism. Dox-gluRDVs can efficiently deliver and accumulate Dox in lysosomes, bypassing drug efflux transporters and facilitating cellular uptake and retention of Dox in drug-resistant MES-SA/Dx5 cells. The transfer of lysosomal calcium to the mitochondria during mitochondria-lysosome contact due to lysosomal Dox accumulation may result in mitochondrial ROS overproduction, mitochondrial membrane potential loss, and activation of apoptotic signaling for the superior anti-MDR activity of Dox-gluRDVs in vitro and in vivo. This work highlights the great promise of RDVs to serve as a bDDS of Dox to overcome MDR cancers but also opens up a reliable strategy for lysosomal-mitochondrial axis-dependent cell death for fighting against other inoperable cancers.